2016
DOI: 10.1007/s12035-016-9705-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Human Transforming Growth Factor-α in Astrocytes

Abstract: Transforming growth factor-alpha (TGF-α) is known to play multifunctional roles in the central nervous system (CNS), including the provision of neurotropic properties that protect neurons against various neurotoxic insults. Previously, we reported that TGF-α mediates estrogen-induced enhancement of glutamate transporter GLT-1 function in astrocytes. However, the regulatory mechanism of TGF-α at the transcriptional level remains to be established. Our findings revealed that the human TGF-α promoter contains con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The NF-κB plays a key role in redox-sensitive signal transduction pathways. According to Karki et al [34], QNZ is a specific inhibitor of NF-κB. In this research, BV2 cells were cultivated in a mixture of QNZ and EC.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB plays a key role in redox-sensitive signal transduction pathways. According to Karki et al [34], QNZ is a specific inhibitor of NF-κB. In this research, BV2 cells were cultivated in a mixture of QNZ and EC.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we found that overexpression of Akt induced TGFα promoter activity, while Akt inhibitor MK2206 downregulated the activity. PI3K/Akt inhibition has been shown to reduce dexamethasone-induced TGFα promoter activity and mRNA levels in astrocytes [ 56 ]. In agreement with this previous observation, we found that MK2206 reduced TGFα production in and release from TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among neuroprotective agents to be tested, the possibility of using growth factors from cord blood arises from a variety of observation in preclinical and clinical studies, for instance, in amyotrophic lateral sclerosis [ 27 ]. We had determined in the CBS eye drops the levels of GFs involved in promoting corneal epithelial healing, but some of them had also been shown to exert neuroprotection mechanism in experimental models of glaucoma, such as TGF- α [ 28 ], b-NGF [ 29 ], and PDGF-bb [ 30 ]. The report only allows us to speculate that these GFs, potentially in a synergic action with others not tested specifically on this occasion, may have played a role in the amelioration of the visual field parameters.…”
Section: Discussionmentioning
confidence: 99%